Reproducibility tests with zinc oxide thick-film sensors. Issue 5 (1st April 2020) - Zonta, G.; Astolfi, M.; Casotti, D.; Cruciani, G.; Fabbri, B.; Gaiardo, A.; Gherardi, S.; Guidi, V.; Landini, N.; Valt, M.; Malagù, C.
Abstract: Reproducibility of the sensor response is one of the fundamental themes for obtaining marketable devices with a high degree of reliability. This parameter becomes decisive especially if the sensor signals are used to identify compound mixtures by means of recognition algorithms. In fact, to apply the same algorithm to different devices, sensors must be identical within a minimum error margin. This point became crucial for medical diagnostic tools, e.g., for cancer screening and monitoring. A set of three thermo-activated thick-film Zinc Oxide (ZnO) sensors, obtained from the same screen-printing deposition, have been tested in laboratory with diverse gases and two biological fecal samples. Fecal samples have been employed in the clinical validation protocol of a device for non-invasive colorectal cancer pre-screening, as emitters of oncologic volatile biomarkers. Sensors showed a good reproducibility degree, with an error lower than 10% of response value for all compounds, reaching 1%–2% for some gases.